Aging of natural rubber studied via Fourier-transform rheology and double quantum NMR to correlate local chain dynamics with macroscopic mechanical response. (24th October 2019) - Nie, Shouliang; Lacayo-Pineda, Jorge; Willenbacher, Norbert; Wilhelm, Manfred
Abstract: Nowadays mainly the linear rheological properties of natural rubber (NR) vulcanizate during aging are studied, even though NR is rheologically nonlinear under most application conditions. Here, the nonlinearity was quantified via Fourier transform rheology (FT-Rheology) using I 3/1, the relative intensity of the 3rd harmonic. The crosslink density and the content of defects were investigated by the 1 H double quantum nuclear magnetic resonance (DQ-NMR). For aerobic aging at 120 °C, the crosslink density increases, but later turns into a broader mesh size distribution with more defects. Accordingly, the rheological nonlinearity of the material increases in the earlier stage and then decreases. For mechanical aging, the nonlinearity continuously decreases as a function of the fatigue cycle numbers, whereas the local crosslink density of the polymer network remains constant. This behavior can be assigned to the micro-cracks generated along adjacent network defects, which are larger than the detection scale of DQ-NMR. Compared to the linear rheological parameters, storage modulus G′ and loss factor tan δ, I 3/1 exhibits higher sensitivity to the aging of crosslinked NR under both high temperature aerobic and mechanical fatigue conditions. Graphical abstract: Image 1 Highlights: The development of rheological nonlinearity of NR during aging has been investigated. The evolution of the crosslink density and defects correlate well to rheological response. The parameter from FT-Rheology I 3/1 exhibits higher relative sensitivity. With the limitations of NMR and microscope, I 3/1 respond to the network change at both nano- and micrometer scales.